Developing effective strategies: A review of past and present government agricultural interventions - Rhoe, Valerie; Sackey, James; Adeogun, Grace (International Food Policy Research Institute, 2009)
After a brief tour of the Mazubi Farms, the retreat began with a welcome by Ms. Valerie Rhoe, Program Coordinator, IFPRI. The welcome address highlighted the importance of updating the FMAWR agriculture strategy based on evidence. Dr. Shashi Kolavalli, former Interim Program Leader, IFPRI, provided the on the status of the agriculture strategy update as of the retreat, which included the FMAWR-World Bank-USAID Stakeholder Forum on Sustainable Agricultural Development Strategy and Food Crisis Response Programme on February 24-25, 2009 and a series of discussions with the National Food Reserve Agency (NFRA) on the process for updating the strategy. It was stressed that IFPRI will facilitate the updating process and generate needed information, but the drafting of the updated strategy is jointly undertaken with FMAWR staff and agriculture experts to ensure those who will implement the strategy are the key players in its drafting. In updating the current strategy, three areas of emphasis to consider are: how to monitor and evaluate its implementation, how to measure what has been achieved, and what institutional changes are needed for its successful implementation.